STUDI EMPIRIS ATAS KUALITAS AUDIT - Anastasia, .; Meiden, Carmel (Proceeding SENDI_U, 2015)
This study aims to determine whether the competence, independence, time budget pressure, and ethicalimpact on audit quality. Research with the theme of quality audit becomes important in two points: first,as a way of seeing reality in compliance auditor to audit standards and the second, while maintaining usertrust. Audit quality on the one hand can increase the reliability of the information, on the other hand isinfluenced by many factors such as the competence, independence, time budget pressure, and ethics. Thisstudy uses the KAP auditor as respondents, by considering two important things: first, in Jakarta and thesecond, the category of non big four, as a way of presenting variation among the existing research. Totalrespondents 106 auditors were selected purposively and proportionally from 17 KAP. The data isprocessed using multiple linear regressions after classical assumption test and instrument questionnairetest. The results showed all four of the above factors have a significant effect on audit quality.Suggestions of this study extend some aspects of the research.Keywords: audit quality competence, independence, time budget pressure, ethics, auditors